Development of ZnO-based sensors for fuel cell cars equipped with ethanol steam-reformer for on-board hydrogen production. Issue 10 (July 2020) - Krishnakumar, T.; Kiruthiga, A.; Jozwiak, E.; Moulaee, K.; Neri, G.
Abstract: In this paper, pure (ZnO) and doped-zinc oxide (Mo- and Cr-ZnO) samples were prepared, characterized and investigated as sensing material with the main objective to develop a conductometric sensor platform that can detect hydrogen and ethanol, for application in fuel cell cars equipped with ethanol steam-reformer for on-board hydrogen production. ZnO-based nanomaterials were synthesized by a simple wet chemical method and characterized by X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. ZnO sample was found to possess a well defined dumbbell-like morphology, while Mo- and Cr-ZnO samples showed non ordered structures at micrometric level. Sensing tests revealed that the sensor response to H2 and ethanol is largely dependent on the temperature, nature and loading of dopant. ZnO-based sensor showed very good performance in terms of sensor response (R0 /R = 10–@2000 ppm of hydrogen), response and recovery time (5 and 7 s, respectively) at the operating temperature of 400 °C, which are promising characteristics for developing an hydrogen leak sensor. The ZnO sensor showed also good characteristics for detecting selectively ethanol when operating at lower temperature (250 °C). On the other hand, the detection of both gases can be also accomplished using two sensors, namely ZnO and Mo-ZnO, operating both at the same temperature of 250 °C. On the basis of the results reported, a single conductometric platform based on these sensors, can be proposed for detecting leak hydrogen as well as both ethanol fuel and hydrogen, for monitoring the steam reforming process efficiency in fuel cell cars.